A critical reflection on improving effective team communication - Yang Hua (Sciendo, 2019)
This paper aims at critically reflecting on the author's personal experience in the context of communication within a nursing team and exploring relevant existing constraints with a view to improving practice and achieving more effective outcomes in team communication.